Dermatomyositis-Associated Interstitial Lung Disease Misdiagnosed as Pulmonary Tuberculosis - Abubakar Sadiq Maiyaki; Aminu Abbas; Ibrahim Abdullahi; Isa Musa Wasagu; Nasiru Aaltine Dankiri; Olisa Ochiagha; Farouk Kabir Umar; Aliyu Abullahi (Nigerian Journal of Medicine)
Dermatomyositis (DM) is a rare idiopathic inflammatory myopathy with hallmark skin manifestations and, in some cases, interstitial lung disease (ILD). This case report presents a 35-year-old male with chronic cough and constitutional symptoms, initially resembling pulmonary tuberculosis (TB). As the condition progressed, the patient developed proximal muscle weakness, arthralgia, Gottron’s papules and the holster sign. Further testing revealed positive antinuclear antibodies, anti-Mi-2, and anti-Jo-1 antibodies, restrictive lung pattern on pulmonary function test and high-resolution computer tomography (HRCT) features of non-specific interstitial pneumonia (NSIP), confirming dermatomyositis-associated interstitial lung disease (DM-ILD). This report discusses the diagnostic challenges posed by DM-ILD when it mimics pulmonary TB and highlights the importance of a comprehensive autoimmune workup in cases with atypical presentations. A timely diagnosis and management of DM-ILD are crucial to prevent disease progression and improve patient outcomes.